Serological Epithelial Component Proteins Identify Intestinal Complications in Crohn's Disease - Yau, Yunki Y. (Mol Cell Proteomics, 2017)
Crohn's Disease (CD) is a relapsing inflammation of the gastrointestinal tract that affects a young working age population and is increasing in developing countries. Half of all sufferers will experience stricturing or fistulizing intestinal complications that require extensive surgical interventions and neither genes nor clinical risk factors can predict this debilitating natural history. We applied discovery and verification phase studies as part of an NCI-FDA modeled biomarker pipeline to identify differences in the low-mass (<25kDa) blood-serum proteome between CD behavioral phenotypes. A significant enrichment of epithelial component proteins was identified in CD patients with intestinal complications using quantitative proteomic profiling with label-free Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS). DAVID 6.7 (NIH) was used for functional annotation analysis of detected proteins and immunoblotting and multiple reaction monitoring (MRM) to verify a priori findings in a secondary independent cohort of complicated CD (CCD), uncomplicated inflammatory CD (ICD), Th1/17 pathway inflammation controls (rheumatoid arthritis), inflammatory bowel disease controls (ulcerative colitis), and healthy controls. Seventy-six high-confidence serum proteins were modulated in CCD versus ICD by LC-MS/MS (p < 0.05, FDR q<0.01), annotating to pathways of epithelial barrier homeostasis (p < 0.01). In verification phase, a putative serology panel developed from discovery proteomics data consisting of desmoglein-1, desmoplakin, and fatty acid-binding protein 5 (FABP5) distinguished CCD from all other groups (p = 0.041) and discriminated complication in CD (70% sensitivity and 72.5% specificity at score ≥1.907, AUC = 0.777, p = 0.007). An MRM assay secondarily confirmed increased FABP5 levels in CCD (p < 0.001). In a longitudinal subanalysis-cohort, FABP5 levels were stable over a two-month period with no behavioral changes (p = 0.099). These studies along the biomarker development pipeline provide substantial proof-of-principle that a blood test can be developed specific to transmural intestinal injury. Data are available via the PRIDE proteomics data repository under identifier PXD001821 and PeptideAtlas with identifier PASS00661.